The healthcare system – a world of work in which numerous occupations are shifting - Jörgens, Julia [Verfasser]; Borowiec, Thomas [Verfasser] (My University, 2026)
"The German healthcare system is experiencing a shift and faces major challenges, particularly as a result of demographic development, a shortage of qualified skilled workers, and economic and technological changes. This has an impact on a number of non-academic healthcare professions. Which professions are affected, and what vocational education and training pathways are required for their training? This article provides an overview of the heterogeneous training landscape in the healthcare system and outlines some reforms which have already been instigated." (authors' abstract; BIBB-Doku)
Keywords: G 1.2.4.2.8 Gesundheits-, Veterinär- und Sozialwesen; S 6.4.5 Gesundheits-, Sozial- und Erziehungsberufe; 370; Gesundheitswesen; Gesundheitsberuf; Berufsausbildung; Rechtliche Regelungen; Interprofessionelle Kooperation; Akademisierung; Quantitative Angaben